APLIKASI TEKNIK ENKAPSULASI PADA BENIH SENGON (Paraserianthes falcataria) - Priadi, Dody (LIPI Press, 2010)
Seeds were encapsulated using materials containing nutrients in order to survive on a deforested land after spreading by aeroseeding technique. Sengon (Paraserianthes falcataria) seeds from Bogor, Tasikmalaya and Garut were encapsulated using mixture of soil, rice bran, tapioca fl our with compost made from leaf waste and manure (3:1) as a nutrients source. Seeds with a good appearance were tested for the moisture content and stratifi ed prior to germination test on tissue paper and grassy and sandy soil to determine the initial germination. Results of initial seeds germination showed that the highest germination (61.7%) on grassy soil obtained by the seeds from Cianjur, while the lowest (39.0%) obtained by seeds germinated on sandy soil. Seed stratifi cation prior to germination causes the capsule damage and early germination. Encapsulated seeds failed to germinate in germination chamber although the capsules already broken. The highest germination percentage (24.7%) and plant height (3.9 cm) obtained from the encapsulated seeds containing media G (100 g soil + 100 g compost + 100 g tapioca fl our) with the exception for total compound leaves and roots. Seeds encapsulated using rice bran causes microbial contamination of seed capsules so that failed to germinate. This study showed that the tapioca fl our was absolutely necessary as an adhesive agent within encapsulate components with seeds, while the compost can enhance plant growth. Contrary the rice bran causes microbial contamination on seed capsules.